2022
DOI: 10.1111/jwas.12921
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of supply of marine finfish species with potential for commercial growth in the United States

Abstract: Global production of marine finfish has grown in total volume of production and the number of species farmed commercially, but there has been little production in the United States of marine finfish other than salmon and red drum. For most species considered to be ready for commercialization, there are few or no farms from which to evaluate the size of the market or to estimate revenues and costs necessary to assess economic feasibility. This present study takes a first step to fill this gap with an analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Revenue estimates were calculated from estimated market prices and yield (i.e., harvested biomass). Current market prices of wild-caught landings are unlikely to be realistic for farmed production for most of the species considered to be candidates for commercialization given the current low volume supplied from the wild (Engle, van Senten, & Schwarz, 2023). Commercial sales of farmed redfish in the United States were used as the basis for developing conservative estimates of relative market prices for the various species considered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Revenue estimates were calculated from estimated market prices and yield (i.e., harvested biomass). Current market prices of wild-caught landings are unlikely to be realistic for farmed production for most of the species considered to be candidates for commercialization given the current low volume supplied from the wild (Engle, van Senten, & Schwarz, 2023). Commercial sales of farmed redfish in the United States were used as the basis for developing conservative estimates of relative market prices for the various species considered.…”
Section: Methodsmentioning
confidence: 99%
“…Economic feasibility of an enterprise depends on market conditions of supply and demand as well as an understanding of production costs. A supply analysis of the marine species identified as candidates 1 for commercialization in the United States showed that current volumes in US markets are low, totaling only 36.6 million kg in 2019 (Engle, van Senten, & Schwarz, 2023). Commercial wild-caught landings have declined for 85% of the marine finfish species identified as candidates for commercialization, and such decreased supply may provide opportunities for aquaculture to fill supply gaps.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid Striped Bass and Red Drum differ from other foodfish species farmed in the USA because of their classification as “gamefish” in many states. Red Drum and Striped Bass (male parent in the genetics cross used most widely to produce sunshine bass in the USA) are popular marine sportfish for which the recreational catch far exceeds the commercial catch (Engle et al 2022b). While other farmed species, such as catfish, at one time competed with commercial and recreational catches, the farmed catfish supply now greatly exceeds that consumed from commercial or recreational catches (Engle et al 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…As relatively new farmed species, HSB and Red Drum farms face regulatory issues related to their status as “gamefish.” Hybrid Striped Bass farming gained a foothold in markets when overfishing of Striped Bass Morone saxatilis in the Chesapeake Bay resulted in various moratoriums and restrictions on the commercial and recreational catch (Andersen et al 2021). Similarly, restrictions on commercial catch of Red Drum have limited the supply to markets, particularly in the Gulf states of the USA (Engle et al 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…They are involved in different activities of the supply chain. While studies report that some people are involved farming, others are involved in harvesting, processing, storing and transportation (Engle et al, 2018). Moreover, at a certain stage, local vendors (intermediaries) buying from local farmers are involved.…”
Section: Introductionmentioning
confidence: 99%